Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1080/00220380500155361
|View full text |Cite
|
Sign up to set email alerts
|

Biased Lending and Non-performing Loans in China's Banking Sector

Abstract: This article uses a panel data set of public listing companies in China empirically to explore the relationship between banks' lending behaviour and non-performing loans. Our results show that state-owned enterprises (SOEs) got more loans than other firms, other things being equal, and SOEs with high default risks were able to borrow more than the low-risk SOEs and non-SOEs. This suggests that Chinese banks had a systemic lending bias in favour of SOEs, particularly those with high default risks, during the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(38 citation statements)
references
References 12 publications
0
37
0
1
Order By: Relevance
“…The results of this study show that the Chinese banks have a structured lending bias towards state-owned enterprises (SOE), especially those with high default risk. The study observes that the high-risk SOE were able to borrow more than the low-risk SOEs and non-SOEs (Lu et al, 2005).…”
Section: Literature Reviewmentioning
confidence: 84%
See 1 more Smart Citation
“…The results of this study show that the Chinese banks have a structured lending bias towards state-owned enterprises (SOE), especially those with high default risk. The study observes that the high-risk SOE were able to borrow more than the low-risk SOEs and non-SOEs (Lu et al, 2005).…”
Section: Literature Reviewmentioning
confidence: 84%
“…The impact on loan categories is obvious with mortgages being the least reactive to changes in the macroeconomic environment. Lu et al (2005) explored the relationship between banks' lending behaviour and NPLs by using the financial data from annual financial reports of all publicly listed companies. The results of this study show that the Chinese banks have a structured lending bias towards state-owned enterprises (SOE), especially those with high default risk.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some of the studies which analyze NPLs of Chinese banks from different perspectives are given below. Lu et al (2007) explored the relationship between Chinese banks' lending behavior and level of NPLs. They used the data from a set of publically listed companies and concluded that state-owned enterprises (SOEs) got more loans compared with other firms.…”
Section: Studies Regarding Non-performing Loansmentioning
confidence: 99%
“…Even if creditors have the incentive to discipline managers of the debtor company, the incomplete legal protection of creditor rights can make it costly for them to enforce discipline (Dharwadkar et al, 2000). Further, in countries like China, all the major banks are owned by the state, and therefore have their own governance problems (Lu, Thangavelu, & Hu, 2005). They cannot be used as an effective monitoring mechanism and will not likely call for divestiture activity in debtor companies.…”
Section: Divestiture and Corporate Debtmentioning
confidence: 98%